ON ERRORS WHEN REPLACING NON-BIFURCATIONAL STABILITY PROBLEMS FOR ELASTIC FRAMES WITH BIFURCATIONAL ONES - Gaik Manuylov; Sergey Kosytsyn; Maxim Begichev (International Journal for Computational Civil and Structural Engineering, 2024)
The method of replacing the existing distributed load with an equivalent load in the form of concentrated forces applied at the nodes is often used in frame stability problems. This replacement of the initial flexural equilibrium with an unbended tension-compression equilibrium introduces certain errors in the calculated values ​​of critical loads. These errors can be of different signs (ie, the calculated "pseudo-bifurcation" critical force can be either greater than the actual one or less than it). The paper demonstrates the errors of such a load change on the example of frame stability problems.